Length of Online Course and Student Satisfaction, Perceived Learning, and Academic Performance - Ferguson, Janet M.; DeFelice, Amy E. (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2010)
This research presents findings from a two-part study. In the first part, graduate students taking online courses were given a course evaluation form. Student responses from online abbreviated summer sessions were compared to student responses from online full-semester courses. Both the intensive and full-semester courses were taught by the same professor and both had identical requirements in terms of assignments and exams. The independent variable was the length of time taken to complete the requirements, with the dependent variables being satisfaction with the course, perceived learning, and academic performance. A statistical analysis of the data found significant differences in a number of areas.